Genome Size Estimation Using Flow Cytometry in Elettaria cardamomum Maton - Anjali, N.; Nadiya, F.; Shefeek, S.; Sabu, K. K. (Indian Forester, 2016)
The relative 2C genome size and total number of base pairs of small cardamom (Elettaria cardamomum Maton) was determined using flow cytometer. Seven accessions of cardamom were included in the present study. Zea mays L. CE-777 (2C=5.43 pg) was found to be the most suitable reference standard. Samples for analysis were prepared following the two step procedure described by Otto and involving Propidium iodide staining. The fluorescence intensity of 5000 particles was recorded. The mean amount of 2C nuclear DNA of the cardamom sample was calculated as 2.84 pg. Conversion between DNA content and genome size (1 pg DNA=980 Mbp) indicate that the diploid genome size of cardamom is 2783 Mbp. This is the first report of DNA content and genome size in cardamom. Low variation in genome size has been observed for various germplasm accessions including wild, released varieties and landraces.